Effect of Vibration on Alleviating Foot Pressure-Induced Ischemia under Occlusive Compression - Weiyan Ren (Hindawi Limited, 2021)
Objectives. Foot ulcers often occur in people with diabetes because of pressure-induced tissue ischemia. Vibration has been reported to be helpful in alleviating mechanical damage and promoting wound healing. The objective of this study is to explore whether vibration can relieve reactive hyperemia in foot tissue under occlusive compression. Methods. Thirteen healthy adults participated in the study. Each foot was placed under occlusive compression without or with vibration intervention, which was randomly assigned every other day. The dorsal foot skin blood flow (SBF) was measured pre- and postintervention for each subject in each test. Temporal variations and spectral features of SBF were recorded for comparison. Results. The results showed that subjects displayed an obvious reactive hyperemia in the foot tissue after pressure occlusion, whereas they displayed a more regular SBF when vibration was applied along with occlusive compression. Moreover, the amplitude of metabolic, neurogenic, and myogenic pathways for SBF was significantly reduced during the hyperemia process when vibration was applied. Conclusions. This study demonstrated that vibration can effectively reduce the level of hyperemia in foot tissue under occlusive compression and also induce less protective physiological regulatory activities. This is helpful for protecting foot tissue from pressure-induced ischemic injury and foot ulcers.